Islamic Educational Approaches to Stunting Prevention and Child Protection - Sri Astuti A. Samad; Munawwarah Samad; Saiful Ramli; Sabriadi HR; Ilyas Ilyas (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Stunting, characterized by impaired growth and development in children under five years old, represents a significant global nutritional issue, particularly in Indonesia. This study aims to explore stunting prevention and child protection from the perspective of Islamic education. Employing a qualitative methodology with a phenomenological approach, the research seeks to understand and interpret specific events and social situations related to stunting and child protection within the Indonesian context. Data were collected through in-depth interviews and documentation, specifically involving lecturers at UIN Ar-Raniry Banda Aceh. The findings reveal that the incidence of stunting in Indonesia remains alarmingly high compared to other middle-income countries, leading to decreased cognitive abilities, heightened health risks, and diminished future productivity. The research concludes that stunting prevention and child protection are critical national programs that require synergistic implementation to secure a better future for children and ensure their right to quality education. From the perspective of Islamic education, these efforts are intrinsically linked, as Islamic teachings emphasize the importance of proper care, provision of halal and nutritious food, which positively influence both the physical and mental well-being of children. The study highlights the need for integrating Islamic educational principles in national stunting prevention strategies to foster holistic child development.